L2 irregular verb morphology: Exploring behavioral data from intermediate English learners of German as a foreign language using generalized mixed effects models - Wagner, Thomas (Studies in Second Language Learning and Teaching, 2017)
This paper examines possible psycholinguistic mechanisms governing stem vowel changes of irregular verbs in intermediate English learners of German as a foreign language (GFL). In Experiment 1, nonce-infinitives embedded in an authentic fictional text had to be inflected for German preterite, thus testing possible analogy driven pattern associations. Experiment 2 explored the psycholinguistic reality of the so-called apophonic path by prompting two inflections for one given nonce-word. Data were analyzed using generalized mixed effects models accounting for within-subject as well as within-item variance. The results of Experiment 1 and 2 support the notion of a pattern associator and yield only scarce evidence for the psycholinguistic reality of a universal apophonic path. Therefore, the organization of irregular verb morphology in the mental lexicon of intermediate GFL learners might best be captured by the linguistic notion of structured lexical entries as well as the psycholinguistic mechanism of an analogy-based pattern associator.